Associations between depression and anxiety in midlife and dementia more than 30 years later: The HUNT Study - Ragnhild Holmberg Aunsmo; Bjørn Heine Strand; Kaarin J. Anstey; Sverre Bergh; Mika Kivimäki; Sebastian Köhler; Steinar Krokstad; Gill Livingston; Fiona E. Matthews; Geir Selbæk (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION It is unclear how midlife depression and anxiety affect dementia risk. We examined this in a Norwegian cohort followed for 30 years. METHODS Dementia status at age 70+ in the fourth wave of the Trøndelag Health Study (HUNT4, 2017–2019, N = 9745) was linked with anxiety and depression from HUNT1 (1984–1985), HUNT2 (1995–1997), HUNT3 (2006–2008), and HUNT4. Longitudinal anxiety and depression score, and prevalence trajectories during 1984–2019 by dementia status at HUNT4 were fitted using mixed effects regression adjusting for age, sex, education, and lifestyle and health factors. RESULTS Dementia at HUNT4 was associated with higher case prevalence at all waves, from 1.9 percentage points (pp) (95% CI: 0.1–3.7) higher at HUNT1 to 7.6 pp (95% CI: 5.7–9.6) higher at HUNT4. DISCUSSION Our findings show that depression and anxiety was more common more than 30 years before dementia onset in those who later developed dementia. Highlights Older individuals with dementia had a higher prevalence of mixed anxiety‐ and depressive symptoms (A + D), both concurrently with and more than three decades prior to their dementia diagnosis. Older individuals with dementia had higher levels of anxiety, both concurrently and up to two decades prior to their dementia diagnosis. Depressive symptoms increased by time among those who developed dementia, but not among others. Results were similar for all cause dementia, Alzheimer's disease, and other types of dementia; however, for vascular dementia, the difference was not significant until dementia was present.